PERAN KOMITMEN INDIVIDU DAN KOMITMEN ORGANISASI DALAM MEMEDASI KORELASI PENGAMBILAN KEPUTUSAN PARTISIPATIF DENGAN KINERJA ORGANISASI (STUDI KASUS PADA UMKM MEBEL DI JEPARA) - maskudi, maskudi (Laporan Penelitian dan Pengabdian Masyarakat, 2024)
ABSTRACTThe purpose of this study was to examine the ability the constructs of individual commitment and organizational commitment to mediate the relationship between the constructs of participatory decision making and organizational performance constructs. The main purpose this research is an applied research descriptive correlative based on data collected which had been done in 2021.The research population consists of employees who work in furniture companies (UMKM) in Jepara. The number of samples taken as many as 141 people, with probability sampling technique.The theoretical frame model that has been made shows the existence of intervening variable, those to test the hypothesis which is already proposed. Hypothesis testing is carried out using Structural Equation Modeling (SEM), using the Analysis of Moment Structure (AMOS).The result of hypothesis’ examination shows that participation on decision making, organizational and individual commitment have a significant positive influence towards organizational performance..Key Words: participatory decision making, organizational commitment, individual commitment, and organizational performance.